1999
DOI: 10.1046/j.1468-2982.1999.019005485.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of Cognitive Habituation and Serotonin Metabolism During the Migraine Interval

Abstract: Migraine patients show a specific cognitive processing with a loss of habituation in the interval and a normal habituation in the attack as measured by event-related potentials (ERPs). It is unknown whether the loss of habituation changes during the migraine interval or is a stable state. Serotonin (5HT) metabolism is involved in the pathophysiology of migraine and also in the generation of ERPs. We enrolled 14 patients with regular migraine attacks in order to measure visually evoked ERPs repetitively during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
132
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 26 publications
14
132
0
3
Order By: Relevance
“…By contrast, during the attack (ie, ictally), habituation and 1st block amplitude increase and normalize, while during the days immediately preceding the attack (ie, preictally), the habituation deficit further worsens. We have postulated that these cortical electrophysiological patterns are related to changes in serotonin transmission, which is low interictally [26], and may further decrease preictally but increase ictally, as suggested by several biochemical studies [27,28] and numerous imaging studies [29,30] showing activation of pontomesencephalic areas comprising monoaminergic nuclei during migraine attacks (see [6] for a review).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, during the attack (ie, ictally), habituation and 1st block amplitude increase and normalize, while during the days immediately preceding the attack (ie, preictally), the habituation deficit further worsens. We have postulated that these cortical electrophysiological patterns are related to changes in serotonin transmission, which is low interictally [26], and may further decrease preictally but increase ictally, as suggested by several biochemical studies [27,28] and numerous imaging studies [29,30] showing activation of pontomesencephalic areas comprising monoaminergic nuclei during migraine attacks (see [6] for a review).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern has been shown for CNV, 36,70,71 VEP, 57,72 and SSEP 61 amplitudes, and for visual P300 latency. 73 The R2 component recorded during blink reflexes-evoked by an electrical stimulus delivered with a classic non nociceptive surface electrode-showed a habituation deficit in patients before a migraine attack, 76 although in another study only slight habituation abnormalities were found interictally. 77 In a longitudinal study of brainstem AEPs, habituation of wave IV-V amplitude was deficient in patients with migraine, but did not change over the migraine cycle.…”
Section: Episodic Migrainementioning
confidence: 93%
“…For instance, cortical responsivity is cyclic in individuals with migraine, 71 and varies in parallel with changes in platelet serotonin content. 73 The period icity of neurophysiological brain activity might also be related to psychophysical, genetic 66,79 or metabolic factors, 80 or to the biorhythms of hypothalamic activity. 81 Migraine periodicity might thus be the result of several inter acting biological cycles.…”
Section: Episodic Migrainementioning
confidence: 99%
“…However, the precise role of 5-HT is not clear (Evers, Quibeldey, Grotemeyer, Suhr and Husstedt, 1999;Ferrari and Saxena, 1993;Fontes Ribeiro, Cotrim, Morgadinho, Ramos, Seabra Santos and Macedo, 1990). During a migraine attack the trigeminal sensory system presumably activates second-order nociceptive neurons within the brainstem, which relay signals to autonomic brainstem nuclei and higher cortical pain processing centres.…”
Section: Serotonin Migraine and Motion Sicknessmentioning
confidence: 99%